The Role of Financial Markets in the Transition Process - Colombo, Emilio; Driffill, John (Physica-Verlag HD, 2003)
Financial Markets play an important role in economic development, channeling saving to investments and facilitating growth. In Eastern Europe financial markets were initially much underdeveloped, and lacked the skills and infrastructure they needed to be efficient, having not acquired them in the pre-transition era. The book offers a both theoretical and empirical analysis of financial markets in transitional economies. It investigates financial markets in Hungary, the Czech Republic, and Poland, and their role in the developments in the 1990s
Keywords: Geschichte 1990-1999; Macroeconomics/Monetary Economics//Financial Economics; Political Economy/Economic Systems; Finance, general; Macroeconomics; Economic policy; Economics; Finance; Kreditmarkt; Wirtschaftsreform; Strukturwandel; Osteuropa; Aufsatzsammlung